Patterns and Personality Correlates of Implicit and Explicit Attitudes Toward Christians and Muslims. - Rowatt, Wade C.; Franklin, Lewis M.; Cotton, Marla (Journal for the Scientific Study of Religion (Wiley-Blackwell), 2005)
We explored implicit and explicit attitudes toward Muslims and Christians within a predominantly Christian sample in the United States. Implicit attitudes were assessed with the Implicit Association Test (IAT), a computer program that recorded reaction times as participants categorized names (of Christians and Muslims) and adjectives (pleasant or unpleasant). Participants also completed self-report measures of attitudes toward Christians and Muslims, and some personality constructs known to correlate with ethnocentrism (i.e., right-wing authoritarianism, social dominance orientation, impression management, religious fundamentalism, intrinsic-extrinsic-quest religious orientations). Consistent with social identity theory, participants' self-reported attitudes toward Christians were more positive than their self-reported attitudes toward Muslims. Participants also displayed moderate implicit preference for Christians relative to Muslims. This IAT effect could also be interpreted as implicit prejudice toward Muslims relative to Christians. A slight positive correlation between implicit and explicit attitudes was found. As self-reported anti-Arab racism, social dominance orientation, right-wing authoritarianism, and religious fundamentalism increased, self-reported attitudes toward Muslims became more negative. The same personality variables were associated with more positive attitudes toward Christians relative to Muslims on the self-report level, but not the implicit level.